A historical perspective on ideas on X-chromosome inactivation - Lyon, Mary (Henry Stewart Talks, 2007)
The phenomenon of X-chromosome inactivation in female mammals, X-chromosome inactivation as a dosage compensation mechanism for equalising the dosage of X-linked gene products in XY males and XX females in somatic cells, inactivity of either the maternal or paternal X-chromosome in different cells in eutherian mammals, preferential inactivation of paternal X in the placenta of mice and in all cells of marsupials, initiation of the process from an X-inactivation centre, discovery of the key gene, Xist, the concept of initiation and maintenance of X-inactivation as separate processes, histone modifications and methylation of CpG islands as maintenance mechanisms, inactivation in autosomal and X-chromosomal DNA, LINE1s as booster elements on the X-chromosome
Archived at 2016/08/31